Pneumothoraks : Definisi Hingga Penatalaksanaan - Khania Atika; Puspa Rosfadilla (Lembaga Pengembangan Kinerja Dosen, 2025)
Pneumothorax is a condition where free air is present in the pleural cavity. Pneumothorax is a life-threatening respiratory emergency that requires immediate treatment. Pneumothorax is classified into 2, namely spontaneous pneumothorax and traumatic pneumothorax. Based on the mechanism of occurrence, namely, open pneumothorax and tension pneumothorax. In general, all types of pneumothorax have almost the same pathophysiological basis. Patients usually come with complaints of shortness of breath, which is sudden and localized in onset. In establishing a diagnosis, anamnesis, physical examination and fast and accurate supporting examinations are needed where the aim is for the management actions given to the patient. General management of pneumothorax is primary survey airway, breathing, circulation. Mortality due to pneumothorax is high if appropriate action is not taken.